QR Out of a Tensed Clause: Evidence from Antecedent‐Contained Deletion. (December 2015) - Syrett, Kristen
Abstract This paper presents an argument based on evidence from experiments featuring Antecedent‐Contained Deletion (ACD) sentences situated in carefully‐manipulated discourse contexts, that covert movement is not grammatically constrained by tense. ACD is a form of Verb Phrase Ellipsis in which ellipsis is embedded in its antecedent. Under an account appealing to Quantifier Raising, the quantificational phrase containing the ellipsis site raises to a VP‐external position, allowing the VP to become the antecedent. When ACD is embedded in a non‐finite clause, such sentences are ambiguous, since multiple VPs can serve as an antecedent. However, when ACD is embedded in a finite clause, the range of interpretations has been claimed to be restricted, because of an independent 'clause‐bounded' movement constraint on Quantifier Raising. However, there are exceptions to this generalization. I present evidence from an experimental investigation of finite‐clause‐embedded ACD sentences, relying on Cecchetto (2004), to demonstrate that under the right discourse conditions, the supposedly unavailable Matrix reading surfaces robustly, at a percentage that is surprising if the constraint were rooted in the grammar. I argue that these results call into question the source of this locality restriction, and propose that it has nothing to do with an arbitrary grammatical constraint on movement.1